Economic benefit of back titration in the treatment of hypertension in Jos, Nigeria - Okeahialam BN; Adeniyi MA (Dove Medical Press, 2017)
Basil N Okeahialam,1 Michael A Adeniyi2 1Department of Medicine, Faculty of Medical Sciences, 2Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmaceutical Sciences, University of Jos, Jos, Nigeria Purpose: Treatment of hypertension is expensive and cost is one of the reasons for inadequate blood pressure control. Where there are no social cost cushions, the burden is borne by patients. With pervasive poverty and inadequate control, complications are unchecked. Back titration in appropriate circumstances should, therefore, translate to economic benefit. This is an attempt to compute, in economic terms, the benefit of back titration.Patients and methods: Thirty-nine patients who entered an antihypertensive back titration program for 12 months and who had been earlier reported on, form the subject of this study. A survey of the cost of antihypertensives in pharmacy outlets in Jos, Nigeria was undertaken. Regimens of antihypertensives that patients were on at the onset and end of the 12 months of back titration were costed in Nigerian currency and compared.Results: Back titration translated to economic benefit in all patients with a cost reduction varying from 2.3% to 100%. This reflected in reduction in mean daily cost of treatment of N107.09–N54.61.Conclusion: The benefit of antihypertensive back titration apart from psychological relief of lower pill burden and side effect profile is in pharmacoeconomics. This permits greater adherence and prevents morbi-mortality consequences of hypertension. In this study, back titration over 12 months translated to average cost reduction of >50%, making treatment more affordable. In appropriate circumstances, back titration of antihypertensives results in economic relief for patients. This should improve adherence, reduce morbi-mortality and is recommended for wider application. Keywords: hypertension, treatment, back titration, pharmacoeconomics, Nigeria